Analisis Penerapan Aplikasi Sistem Keuangan Desa (Siskeudes) dalam Pengelolaan Keuangan Di Desa Banyudono Kecamatan Dukun - Alqi Faizah; Retno sari (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study aims to describe the effectiveness and obstacles or constraints of the application of the village financial system application (siskeudes) in financial management in Banyudono Village, Dukun District. This study uses a qualitative approach with a qualitative descriptive type of research. The data used comes from the results of interviews with the Banyudono Village. The data analysis uses data reduction, data presentation and data verification. The results show that the application of the village financial system application (siskeudes) in Banyudono Village, Dukun District has implemented this application since 2018. For its application it has been quite effective in helping in financial management and in its management it is in accordance with village financial management procedures or standards, but in operation there are still obstacles that do not have a significant effect, one of which is the existence of an error system when it is being used. The village financial system is very important in village governance where a good village financial management system will create optimal accountability and transparency.